2012
DOI: 10.17221/8/2012-jfs
|View full text |Cite
|
Sign up to set email alerts
|

How much birch (Betula papyrifera) is too much for maximizing spruce (Picea glauca) growth: a case study in boreal spruce plantation forests

Abstract: Interest in conifer-broadleaf mixedwood forests has greatly increased due to continuous demand for hardwood products and a shift towards more biological or ecosystem-based management. In British Columbia, more than 30% of the productive forest land is a conifer-broadleaf mixture and current forest regulations are more conifer biased rather than maintaining a mixed-species condition. The aim of this study was to examine the impact of paper birch on white spruce growth. Spruce growth data from 10 to 18 years old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…In case of higher (40% of basal area removed) thinning intensity (Yücesan , the former rich diameter structure of beech stands was equalized. Our results showed higher periodic diameter increment on thinned plots compared to controls; it supported partly the conclusions from mixed pine/ spruce stands (Olson et al 2012), aspen/fir stands (Prévost, Gauthier 2012) or birch/spruce stands (Hawkins et al 2012). All above-mentioned studies found that pre-commercial thinning increased basal area increment.…”
Section: Discussionsupporting
confidence: 89%
“…In case of higher (40% of basal area removed) thinning intensity (Yücesan , the former rich diameter structure of beech stands was equalized. Our results showed higher periodic diameter increment on thinned plots compared to controls; it supported partly the conclusions from mixed pine/ spruce stands (Olson et al 2012), aspen/fir stands (Prévost, Gauthier 2012) or birch/spruce stands (Hawkins et al 2012). All above-mentioned studies found that pre-commercial thinning increased basal area increment.…”
Section: Discussionsupporting
confidence: 89%
“…This suggested that the retention of broadleaves up to a threshold density level in the conifer forest may increase the total productivity of stands. Some other studies in the central BC interior (Hawkins, Dhar 2011;Hawkins et al 2012a) showed that the threshold density of birch in spruce-birch mixed stands was within 3,000-4,000 stems·ha -1 in 10 to 18 years old stand. Moreover, they also reported that spruce-birch mixed stands are more productive than the single species stand.…”
Section: Discussionmentioning
confidence: 92%
“…This is consistent with the observations of Valkonen and Valsta (2001), who suggested a small negative effect of birch on Norway spruce growth. Based on the study by Fahlvik et al (2005) and Hawkins et al (2012a), the productivity of birch and spruce mixture was greater compared to Norway spruce or white spruce monocultures. The Scandinavian experience shows that birch-spruce mixtures are more productive than spruce alone until the age of ca 20 years and thereafter, spruce monocultures are usually more productive (Frivold, Frank 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations